MENINGKATKAN KEMAMPUAN SISWA DENGAN METODE CERAMAH DAN TANYA JAWAB DI SD NEGERI 094099 SIRUBE-RUBE - Sohnata Hutauruk, Bertaria; Tua Saragih, Paham; Hutahaean, Trisnawaty; Betharia Situngkir, Esra; Dewi Nagur, Melani; Chatrine Simbolon, Joice; Togi Hutahaean, David (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The service community activity aims to improve the students’ ability in learning through lecturing and Questioning-answering in SDN 094099 SIRUBE-RUBE.  The significance of the service community activity is: The students get the improvement and knowledge in learning the whole subject at school. The activity is done throug taking course after school around 15 to 17 pm every Monday to Friday. There are 6 classes which consists of 25 studentds per class.  The method which is done in this service community activity is giving all subject course in BIMBEL (Bimbingan belajar) face to face in the classroom. The teaching started by identifying the students’ difficulties and needs from the school for example theme topic from the book, homework and analysis of the material based on the textbook, arranging the schedule of the students, monitoring and evaluation of the whole ativity. In the teaching, the method which has been applied is lecturing and questioning-answering to the students in the classroom. The activity of service community  is finally end up because of the help from the stakeholders: (1) cooperation with the team of serice community with the advisor from HKBP Nommensen University with the village headma Sirube Rube, (2)  The principal of SDN Sirube Rube, (3) the available of location Sirube-Rube, (4) Available place of the course (BIMBEL). The conclusion is that the service community activity ends up well. It can be seen from the the result of the students’ ability has an improvement from the monthly report test at school. The students also eager to learn and antusiasm to learn the whole subject at school. They are very active in questioning and answering the teachers’ questions in the process of teaching and learning in the classroom. The suggestion of the activity is hoped that there will be a next service community activity program to be continued by the other team from the school, university or other institution to do the same activity so the students can feel motivated and still anstusiasm to  learn through BIMBEL.